Pyrrolizine-5-carboxamides: Exploring the impact of various substituents on anti-inflammatory and anticancer activities - Gouda Ahmed M.; Abdelazeem Ahmed H.; Abdalla Ashraf N.; Ahmed Muhammad (Acta Pharmaceutica)
Towards optimization of the pyrrolizine-5-carboxamide scaffold, a novel series of six derivatives (4a-c and 5a-c) was prepared and evaluated for their anti-inflammatory, analgesic and anticancer activities. The (EZ)-7-cyano-6-((4-hydroxybenzylidene)amino)-N-(p-tolyl)-2,3-dihydro-1H-pyrrolizine-5-carboxamide (4b) and (EZ)-6-((4-chlorobenzylidene)-amino)-7-cyano-N-(p-tolyl)-2,3-dihydro-1H-pyrrolizine-5-carboxamide (5b) bearing the electron donating methyl group showed the highest anti-inflammatory activity while (EZ)-6-((4-chlorobenzylidene)amino)-7-cyano-N-phenyl-2,3-dihydro-1H-pyrrolizine-5-carboxamide (5a) was the most active analgesic agent. Cytotoxicity of the new compounds was evaluated against the MCF-7, A2780 and HT29 cancer cell lines using the MTT assay. Compounds 4b and 5b displayed high anticancer activity with IC50 in the range of 0.30–0.92 μmol L−1 against the three cell lines, while compound (EZ)-N-(4-chlorophenyl)-7-cyano-6-((4-hydroxybenzylidene)-amino)-2,3-dihydro-1H-pyrrolizine-5-carboxamide (4c) was the most active against MCF-7 cells (IC50 = 0.08 μmol L−1). Both the anti-inflammatory and anticancer activities of the new compounds were dependent on the type of substituent on the phenyl rings. Substituents with opposite electronic effects on the two phenyl rings are preferable for high cytotoxicity against the MCF-7 and A2780 cells. COX inhibition was suggested as the molecular mechanism of the anti-inflammatory activity of the new compounds while no clear relationship could be observed between COX inhibition and anticancer activity. Compound 5b, the most active against the three cell lines, induced dose-dependent early apoptosis with 0.1–0.2 % necrosis in MCF-7 cells. New compounds showed promising drug-likeness scores while the docking study revealed high binding affinity to COX-2. Taken together, this study highlighted the significant impact of the substituents on the anti-inflammatory and anticancer activity of pyrrolizine-5-carboxamides, which could help in further optimization to discover good leads for the treatment of cancer and inflammation.